The implementation of quality management in brazilian building design firms - Grilo, Leonardo Melhorato (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
The lack of quality in building design has been pointed out as one of the most important barriers for technological and organizational improvement in the Brazilian construction industry. Although different approaches for design improvement have been described in literature, this research focuses specifically on the implementation of quality management systems in design firms. This paper analyses the impact of quality management in Brazilian design firms and highlights the motivations, expectations and difficulties that have arisen during implementation. The research method involved case studies, which consisted of interviews with design firm’s principals. Despite the improvements obtained, mainly in firms with certified quality management systems, deficiencies in strategic processes were identified during the interviews and are discussed in detail in this paper.